Promoting public health using competition law: applying the essential facilities doctrine to increase access to drugs in South Africa - Ntambirweki, Barbara (Centre for Law and Society, 2026)
The impact and nature of HIV/ AIDS pandemic epitomizes the greatest threat to public health and the most important challenge facing South Africa today.1 In 2007, it was estimated that more than five million people are living with HIV/ AIDS in South Africa which represents the highest number of sufferers in any country in the world. 2 It is likely that close to 400,000 South Africans die of the disease each year.3 Despite this reality, the government for sometime was reluctant to deal with urgency and commitment required by the epidemic.4 After many years of controversy with civil society, the government fina11y adopted a new National HIV/ AIDS & STI Strategic Plan for South Africa 2007-11 (NSP). The primary aims of the NSP is to reduce the rate HIV infections by 50% by 2011 and reduce the impact of AIDS by expanding access to appropriate treatment care and support to 80% of those in need by 2011. The four priority areas of NSP include prevention, treatment, care, support; research monitoring and surveillance.